Enlarged perivascular spaces in the basal ganglia mediate the negative impact of HbA1c levels on mild cognitive impairment - Liu, Cuicui; Liu, Wanhu; Yang, Yimeng; Xu, Yuzhu; Li, Wenjun; Wang, Jinyang; Ren, Huiling; Liu, Junyan (Frontiers in Human Neuroscience, 2025)
BackgroundThis study aimed to investigate the mediating effect of enlarged perivascular space (EPVS) in basal ganglia (BG) on the relationship between glycated hemoglobin (HbA1c) levels and mild cognitive impairment (MCI) in patients with cerebral small vessel disease (CSVD).MethodsData on HbA1c levels and MOCA scores and CSVD imaging markers, including EPVS volume and distribution patterns were collected. Logistic regression was performed to identify independent risk factors for MCI. A mediation effect analysis was further conducted to determine whether BG-EPVS mediate the impact of HbA1c on cognitive impairment.ResultsA total of 244 CSVD patients were enrolled in this study. Compared with non-DM patients, DM patients had a significantly greater BG-EPVS volume (p < 0.001) and more severe periventricular white matter hyperintensities (p-WMH) (p = 0.036). Multivariate logistic regression analysis revealed that hypertension [odds ratio (OR) = 3.823; 95% confidence interval (CI):1.707–8.566; p = 0.001], the HbA1c level (OR = 1.689; 95%CI:1.255–2.272; p<0.001) and BG-EPVS volume (OR = 1.001; 95% CI:1.000–1.003; p = 0.038) were independent risk factors for MCI. After adjusting for sex and age, partial correlation analysis revealed a significant positive correlation between BG-EPVS volume and HbA1c (β = 0.137; p = 0.042) and a significant negative correlation with MOCA scores (β = −0.160; p = 0.013). The effect of HbA1c on MCI in patients with CSVD was indirectly mediated by BG-EPVS volume (indirect effect = −0.074; 95% CI: −0.187 to −0.012; the mediating effect ratio was 11.3%).ConclusionHbA1c is an independent risk factor for MCI. Increased BG-EPVS volume mediates the partial effect of HbA1c on CSVD-related cognitive dysfunction.